CURRENT RATIO, TATO, DAN DEBT TO EQUITY RATIO DALAM MEMENGARUHI HARGA SAHAM SERTA DAMPAKNYA BAGI NILAI PERUSAHAAN BANK YANG TERDAFTAR DI BEI TAHUN 2021- 2023 - Wahyuni, Hafida Aisa; Pramesthi, Riska Ayu; Ariyantiningsih, Febri (Fakultas Ekonomi dan Bisnis, 2025)
This research aims to analyze the influence of the Current Ratio, TATO (Total Asset Turnover), and Debt to Equity Ratio on Firm Value through Stock Prices, in banking companies listed on the Indonesia Stock Exchange (IDX) for the period 2021-2023. The method used is a quantitative approach. The sampling technique employed purposive sampling, resulting in a sample of 12 companies from a total population of 46. The data used is secondary data in the form of annual financial reports published through the official website www.idx.co.id. Data analysis was conducted using the Partial Least Square (PLS) analysis technique via SmartPLS software version 3.0. Based on the PLS test results, it was found that the Current Ratio has a positive but insignificant effect on Stock Prices, TATO has a positive and significant effect on Stock Prices, and the Debt to Equity Ratio has a positive but insignificant effect on Stock Prices. The Current Ratio, TATO, and Debt to Equity Ratio have a positive but insignificant effect on Firm Value, however, Stock Prices have a positive and significant effect on Firm Value. The Current Ratio has a positive but insignificant effect on Firm Value through Stock Prices. TATO has a positive and significant effect on Firm Value through Stock Prices. The Debt to Equity Ratio has a positive but insignificant effect on Firm Value through Stock Prices.